Empowering Diversity: A Case Study on Inclusive Assessment and Universal Design for Learning in a Post-Secondary Programme for Students with Intellectual Disabilities - Camedda, Donatella; Banks, Jennifer; Ringwood, Barbara (My University, 2024)
This paper addresses inclusive assessment and Universal Design for Learning (UDL) for students with intellectual disabilities in higher education. Inclusive assessment entails the creation and application of assessment methods and practices that are both fair and effective, allowing every student to showcase their complete capabilities in terms of knowledge, comprehension, and skills. Universal Design for Learning (UDL) is an instructional approach designed to make curriculum and learning more accessible for every student. Presenting findings of a case study from a post- secondary education programme for students with intellectual disabilities in an Irish university, this article aims to contribute to the knowledge gap existing on this topic in the current literature. The study explored students’ perspectives on inclusive assessment which had been designed and implemented using a UDL approach in a two-year full time Level 5 National Framework of Qualifications (NFQ) course. Adopting a mixed-method approach, the students were invited to take part in two focus groups and to complete an online anonymous qualitative survey structured in an easy-to-read format. The survey and focus group findings provided valuable insights into student perspectives on assessment within the course, designed on UDL principles. Students recognized the multiple means approach in assessment as beneficial, enabling them to express learning without extra accommodations. Challenges cited include time management, assignment preference, and system consistency. Despite occasional anxiety, students felt empowered by engagement with assessments. Suggestions for improvement included more regular feedback, consistency in coursework management, and diverse assignment delivery options. The results of the case study underscored the significance of student voice regarding assessment, emphasising its invaluable role in advancing inclusive practices within a curriculum that adopts a UDL-based approach.
PUBLISHED
Keywords: Inclusive assessment, Intellectual disabilities, Post-secondary education, UDL; Inclusive Society; Higher Education; INTELLECTUAL DISABILITY; Inclusive Education